A Staged Hybrid Procedure to Manage Complex Cerebral Hypoperfusion in Aortic Arch Aneurysm. Issue 10 (2nd September 2015) - Hernández Carbonell, Teresa; Haulon, Stephan; Prat, Alain; Martin‐Gonzalez, Teresa; Tyrrell, Mark R.; Sobocinski, Jonathan
ABSTRACT We report the management of a patient who had an open‐surgical repair following traumatic avulsion of the supra‐aortic trunks (SAT) 30 years prior to presentation with a large arch aneurysm and poor cerebral collaterals. "Simple" thoracic endovascular aneurysm repair (TEVAR) was not an option because it would have excluded the collateral circulation to the carotid and vertebral arteries. We devised a two‐stage hybrid procedure to repair this challenging aneurysm. doi: 10.1111/jocs.12630 (J Card Surg 2015;30:761–763)